Pulse potential deposition of thick polyvinylpyridine-like film on the surface of titanium nitride. Issue 84 (26th August 2016) - Zeb, Gul; Tri, Phuong Nguyen; Palacin, Serge; Le, Xuan Tuan
Abstract : We achieved covalent attachment of a thick polyvinylpyridine-like polymeric film on a 200 mm diameter titanium nitride wafer (MEMS industry standard) using a simple electrochemical setup. Abstract : Electrografting based on the reduction of diazonium salts has been conventionally performed at the laboratory scale with cyclic voltammetry using a typical three-electrode electrochemical system. However, this promising coating technique still needs simplification for industrial feasibility. In this work, we report that pulse potential deposition, using an only two-electrode system, is a powerful tool for the grafting through diazonium chemistry. Importantly, this method allows the covalent attachment of a 135 nm thick polyvinylpyridine-like polymeric film on a titanium nitride wafer of industrial dimensions (200 mm diameter) using an acidic solution of 4-nitrobenzenediazonium and vinylpyridine monomer. Success in grafting suitable polymer films with well-controlled thickness on real engineering materials, such as titanium nitride, opens the door for many novel applications in micro-electromechanical systems (MEMS).